Alternative to Off-Season Sugar Supplement Feeding of Honeybees - Neupane, KR; Thapa, RB (Journal of the Institute of Agriculture and Animal Science, 2005)
An experiment was conducted at Gorkha Bee Farm, Yagyapuri, Chitwan during rainy season of 2005 to investigate alternative to sugar supplement feeding and reduce cost feeding during off- season. Apis mellifera L. honeybee colonies were prepared with 5 frames of covering bees and 3.5 frames of broods and a queen of similar quality each of five different supplemental feedings: i) sugar syrup (1:1 sugar and water); ii) rice bran syrup (100 gm rice bran soaked in 1 lit water and after 4 hours blended, filtered and added 200 gm sugar + 20 gm honey and required water to make 1 lit); iii) maize syrup (100 gm maize flour soaked in 1 lit water and after 4 hours blended, filtered and added 200 gm sugar + 20 gm honey and required water to make 1 lit); iv) banana syrup (100 gm ripen peeled banana mixed in 1 lit water, blended, filtered and added 200 gm sugar + 20 gm honey and required water to make 1 lit); and v) pumpkin syrup (100 gm boiled pumpkin after removing outer hard core mixed in 1 lit water, blended, filtered and added 200 gm sugar + 20 gm honey and required water to make 1 lit) was placed inside the hive in a division board feeder @ 30 ml per frame of honeybees per day at an interval of 3 days. Feeding honeybees with sugar syrup increased number of brood cells by 53.5%, brood frames by 37.1% and frames covered by bees by 32.0%. Honeybee colonies when fed with banana and pumpkin syrup increased brood cells by 16.3% and 2.8%, brood frames by 17.1% and 8.6% and bees covered number of frames by 12.0% and 3.2%, respectively. Number of brood cells, brood frames and covered frames by bee remained almost constant when honeybees fed with pumpkin syrup. On the other hand, feeding bee colonies with maize and rice bran syrup decreased the number of brood cells by 11.2% and 35.2%, brood frames by 11.4% and11.4% and bees covered frames by 24.0% and 24.0%, respectively. The cost of off-season feeding was the highest (Rs. 247.0) for sugar syrup followed by maize syrup (Rs. 140.4), banana syrup (Rs. 117.4), rice bran (Rs. 113.4), and pumpkin syrup (Rs.105.4). All of the feeding materials were safe to bee feeding. Banana syrup feeding was found superior to others, and therefore, its supplementation can reduce the cost of sugar feeding by more than 50% and increase brood production during off-season. Key words: Off- season, honeybee feeding, sugar supplement J. Inst. Agric. Anim. Sci. 26:77-81 (2005)